The Impact Of The Digital Era On The Mental Health Of Generation Z - Syari Fitrah Rayaginansih; Siti Cahyati; Irfan Fahriza (Journal of Education and Counseling (JECO), 2024)
Generation Z grows and develops in a dynamic digital era so that technology itself becomes an integrated part of daily life. In a survey conducted by the Internet Service Providers Association (APJII) in 2024 based on age, Indonesia's highest internet penetration is generation Z (2997-2012) at 34.40%. However, high mastery of technology and social connections provide an unfavorable side to Generation Z such as increased stress, in a study conducted by the Institute Public de Sondage d'Opinion Secteur (IPSOS) it was said that out of 23,274 respondents, as many as 43% of Generation Z experienced higher stress than other generations. The purpose of this study is to review the literature related to the high impact of technology use on mental health. The results show that the regular use of technology can have a two-sided impact on its users, social support, mental health information and opportunities to express themselves are positive impacts that can be obtained, while cyberbullying, FOMO (Fear of Missing Out), increased anxiety and stress, and body image issues, are challenges that will be faced by technology users.